Civil Law Implications for Children Born Through Surrogacy (Surrogate Mother) - Thalib, Sabrina Riyadh; Marsal, Irsyaf (Journal of Law, Politic and Humanities, 2025)
This study analyzes the legal status of children born from surrogacy in Indonesia, a practice considered illegal yet a potential solution for infertility, creating a serious rechtsvacuüm. The research objective is a juridical analysis of this issue under Indonesian civil law using a normative juridical method. The findings indicate that surrogacy agreements are legally invalid and considered null and void (van rechtswege nietig) because they fail to meet the "lawful cause" requirement stipulated in Article 1320 in conjunction with Article 1337 of the Civil Code. This legal void creates uncertainty for the child. Based on the principle of mater semper certa est, the surrogate is legally recognized as the mother, disregarding genetic parentage. This situation infringes upon the child's fundamental rights to identity and inheritance, undermining the principle of pro bono infantis. The study concludes that there is an urgent need for definitive state regulation, either through a strict prohibition or by permitting altruistic surrogacy under rigorous judicial oversight, to provide legal certainty and paramount protection for the child